Integrated Assessment of Water Resources and Global Change A North-South Analysis - Craswell, Eric; Bonnell, Mike; Bossio, Deborah; Demuth, Siegfried; van de Giesen, Nick (Springer Netherlands : Imprint: Springer, 2007)
How can the Earth's finite water resources be managed sustainably to meet the growing needs of humans and of nature in ways that avert the looming crisis? The need to find answers to this question has exercised the minds of many scientists, practitioners and policymakers who recognise the urgency of the problems. These concerns have spawned a number of international research initiatives and programs, prominent representatives of which met to review progress and exchange views at an international conference in Bonn, Germany in February 2005. The pressing water problems must clearly be tackled from an integrated perspective taking into account environmental, human and technological factors and especially their interdependence. The key papers in this volume from the Bonn conference focus on the challenges of integrated assessment of water resources in the context of global change. The growing gap between North and South is also addressed, in terms not only of access to water and its quality, but also of the capacity to do research and implement solutions. The coverage of the papers is up-to-date and comprehensive. Highlights include emerging concepts such as blue and green water, virtual water, the water footprints of nations, multi-agent modelling, linkages between water and biodiversity, and social learning and adaptive management. Audience: Policy-makers, practitioners and researchers concerned with integrated water resources management; scientists from physical, biological, ecological, and social sciences involved in research on global environmental change and natural resources; scientists concerned with water resources in developing countries.